IMPLEMENTASI PROMOSI BAURAN KOMUNIKASI PEMASARAN KARTU KREDIT DI INDONESIA (Studi Deskriptif Bank Mandiri, HSBC, Citibank, BCA dan BNI): Ilham Prisgunanto - Ilham Prisgunanto (Commed : Jurnal Komunikasi dan Media, 2018)
Credit cards are one of the most familiar payment tools for information society. They used integrated marketing communications method to get new costumers. They prepared this method to market expansion. Intergrated marketing communication depend on understanding of company about marketing of communication. This research aims to explore implementation of used integrated marketing communications. This research used theory of marketing communication, theory of integrated marketing communications, promotion and marketing plan. This reaearch method is qualitative descriptive. They collected data from staff and management of bank who produce credit card used interview method (Mandiri, HSBC, BCA, Citibank dan BNI). The result is Local Banks which produce credit card did same promotion method with the International bank method. The big issue about credit card is They must used international big brand from Citibank to arrange their system. The Marketing communication is success because of pattern of organization, cross sectoral integration in corporate. Because of that situation, its important to marketing communication at banking.